2007
DOI: 10.1086/521875
|View full text |Cite
|
Sign up to set email alerts
|

High Spatial Resolution Observations of Two Young Protostars in the R Corona Australis Region

Abstract: We present multiwavelength, high spatial resolution imaging of the IRS 7 region in the R Corona Australis molecular cloud. Our observations include 1.1 mm continuum and HCO + J ¼ 3 ! 2 images from the Submillimeter Array (SMA), 12 CO J ¼ 3 ! 2 outflow maps from the DesertStar heterodyne array receiver on the Heinrich Hertz Telescope (HHT), 450 and 850 m continuum images from SCUBA, and archival Spitzer IRAC and MIPS 24 m images. The accurate astrometry of the IRAC images allow us to identify IRS 7 with the cen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
112
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(132 citation statements)
references
References 36 publications
20
112
0
Order By: Relevance
“…The membership count is probably close to complete for spectral types between B9 and M6, considering that the cluster has been observed in the optical, X ray, IR, and submillimeter (e.g. López-Martí et al 2005Groppi et al 2004Groppi et al , 2007Peterson et al 2011;Sicilia-Aguilar et al 2008, 2011a. Taking into account only the number of stars and not their mass, we arrive to a stellar density of about 3000 stars/pc 3 .…”
Section: What Drives Disk Evolution and Dispersal In Tr 37? Clues Fromentioning
confidence: 67%
“…The membership count is probably close to complete for spectral types between B9 and M6, considering that the cluster has been observed in the optical, X ray, IR, and submillimeter (e.g. López-Martí et al 2005Groppi et al 2004Groppi et al , 2007Peterson et al 2011;Sicilia-Aguilar et al 2008, 2011a. Taking into account only the number of stars and not their mass, we arrive to a stellar density of about 3000 stars/pc 3 .…”
Section: What Drives Disk Evolution and Dispersal In Tr 37? Clues Fromentioning
confidence: 67%
“…Therefore, we fixed the parameters H 0 and R 0 to the typical values of H 0 = 0.1 AU and R 0 = 10 AU. As total disk mass, we assume M disk = 0.012 M (Groppi et al 2007) with a standard gas-to-dust ratio of 100:1. Besides the luminosity L which is incident on the disk rim, the most sensitive parameter in the IN05 model is .…”
Section: Curved Rim Modelmentioning
confidence: 99%
“…The locations of the sources are shown on Spitzer 4.5 μm (Peterson et al 2011) image data, with Herschel 70 μm (Lindberg et al, in prep. ) and SMA 1.3 mm (Chen & Arce 2010) continuum A&A 548, A24 (2012) Peterson et al (2011), (2) Groppi et al (2007), (3) Choi et al (2008), (4) Miettinen et al (2008), (5) Forbrich et al (2006), (6) Nutter et al (2005), (7) Chen & Arce (2010). (b) The coordinates come from SMA and Spitzer continuum reported in Peterson et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nutter et al (2005) studied the region in submillimetre, and detected three peaks within the region around IRS7: SMM 1B coinciding with IRS7B, SMM 1C coinciding with Brown 9, and SMM 1A south of IRS7B. Studies of millimetre continuum emission showed three compact sources, IRS7B (SMM 1B), SMM 1C, and SMM 2 (Groppi et al 2007;Chen & Arce 2010;Peterson et al 2011). Groppi et al (2007) used Spitzer IRAC data, SCUBA 450 μm and 850 μm, and SMA 1.1 mm data to study the SEDs of IRS7B (SMA1) and SMM 1C (SMA2; not detected in the Spitzer data).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation